2015
DOI: 10.1186/s40199-015-0132-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved intraocular bioavailability of ganciclovir by mucoadhesive polymer based ocular microspheres: development and simulation process in Wistar rats

Abstract: BackgroundThe poor ocular bioavailability of the conventional eye drops is due to lack of corneal permeability, nasolacrimal drainage and metabolic degradation. To overcome this issue, drug encapsulated in mucoadhesive polymer based ocular microspheres have the advantages of improved drug stability, easy administration in liquid form, diffuse rapidly and better ocular tissue internalization.MethodsThe ganciclovir chitosan microspheres (GCM) were prepared by modified water-in-oil emulsification method. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…At the end of week 6, the patients were reviewed in the clinic, 3.0 hours following the last application of the ganciclovir gel. As the half-life of ganciclovir is 3.5 to 4 hours [ 17 , 18 ], we sampled the aqueous humor 3.0 hours following the last application of the gel. At this study visit, the patients were asked to verbally confirm the gel application time and quantum before proceeding.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of week 6, the patients were reviewed in the clinic, 3.0 hours following the last application of the ganciclovir gel. As the half-life of ganciclovir is 3.5 to 4 hours [ 17 , 18 ], we sampled the aqueous humor 3.0 hours following the last application of the gel. At this study visit, the patients were asked to verbally confirm the gel application time and quantum before proceeding.…”
Section: Methodsmentioning
confidence: 99%
“…Recently ganciclovir chitosan microspheres (GCM) were prepared and evaluated in Wistar rats (69). In vitro release study exhibited initial burst (nearly 50 %) in first few minutes.…”
Section: Pharmacokinetics Of Various Ophthalmic Formulationsmentioning
confidence: 99%
“…C max of GCM was 2.69-fold higher than ganciclovir group (p < 0.0001) and the delay in T max inferred the sustained release of GCM. It was concluded that the incorporation of ganciclovir into microspheres significantly enhanced relative ocular bioavailability (70). …”
Section: Pharmacokinetics Of Various Ophthalmic Formulationsmentioning
confidence: 99%
“…Moreover, chitosan also holds other special characteristics suitable for ocular drug delivery including nontoxic, low eye irritation, mucoadhesive, in situ gelling, transfection and permeation enhancing properties. All of these advantages contribute to the applications of SACPNs as suitable ocular deliver vehicles (Kapanigowda et al, 2015;Werle & Bernkop-Schn€ urch, 2008. Fox instance, amphotericin-B is encapsulated in SACPNs for prolonged ocular application (Chhonker et al, 2015).…”
Section: Ocular Deliverymentioning
confidence: 99%